Design of Crank Rocker Type Climbing Stair Device - Ruigang Han (Jixie chuandong, 2021)
Aiming at the problem that the stability index r value of star-wheel climbing mechanism is large， which affects the operation stability， a kind of crank rocker climbing stair device is proposed. The influence of crank rocker mechanism rod length on trajectory is studied. The structure size of the crank rocker type climbing mechanism is designed while the r is reduced by 22%.The modeling of crank rocker type climbing stair device and the simulation of the process of climbing stairs are carried out by SolidWorks software， the motion trajectory diagram when the vehicle is unloaded and loaded is obtained， the feasibility of the scheme is determined. A prototype test is carried out to verify the stable operation of the device. The results show that the design idea of crank-rocker stair climbing device is correct， and it has reference significance for developing similar products.